Pengaruh Penerapan Akuntansi Sektor Publik, Good Governance Dan Pengawasan Internal Terhadap Kinerja Instansi Pemerintah - Neneng Karlina; Trisna Sary Lewaru; Dwi Kriswantini (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to determine, and obtain empirical evidence about the effect of public sector financing, good governance and internal control on government performance in OPD South Buru district on Maluku Province. The population in this study is the employees who work in Regional Apparatus Organization (OPD), in South Buru Regency,Maluku Province. This research models uses descriptive quantitative, with data sources in the form of primary data. The sample used in this study was selected through the purposive sampling method with a total sample of 100 respondents. Hypothesis testing in this study using multiple linear regression analysis with the help of SPSS version 16. The results of the study show that the results of the public accounting sector and good governance have a significant effect on the performance of government agencies in South Buru Regency. Whereas, internal control does not have a significant impact on the performance of government agencies in South Buru Regency, on Maluku Province.